2022
DOI: 10.1038/s41598-022-18628-4
|View full text |Cite
|
Sign up to set email alerts
|

Birth related parameters are important contributors in autism spectrum disorders

Abstract: Autism spectrum disorders is a group of childhood onset neurodevelopmental disorders affecting millions of children across the globe. Characterised by age inappropriate lack of reciprocal social interaction, repetitive behaviours and deficits in communication skills, it has been found to have genetic, epigenetic and environmental contributions. In this work, we wanted to identify the effects of birth related parameters on the disease pathogenesis in an exposed population of West Bengal, India. We have consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…The literature revealed that birth order was significantly associated with ASD phenotype, and with the increase in birth order, mental retardation, intelligence score, and adaptive functioning decreased [32,33]. Another research conducted in West Bengal, India, found that children with high birth order have a severe phenotype of autism, while the child born in first order has less phenotype of ASD [34].…”
Section: Plos Onementioning
confidence: 99%
“…The literature revealed that birth order was significantly associated with ASD phenotype, and with the increase in birth order, mental retardation, intelligence score, and adaptive functioning decreased [32,33]. Another research conducted in West Bengal, India, found that children with high birth order have a severe phenotype of autism, while the child born in first order has less phenotype of ASD [34].…”
Section: Plos Onementioning
confidence: 99%
“…The term “autism spectrum disorder” (ASD) encompasses heterogeneous neurodevelopmental conditions characterized by delayed development, early-onset deficits in social communication, and restricted, repetitive sensory-motor behavior of variable significance [ 1 ]. The causes of ASD include a complex combination of genetic and environmental factors and birth-related parameters that may act in concert during the development of the neural system [ 2 , 3 ]. Although the pathophysiology of psychiatric diseases, including ASD, is far from being fully elucidated, a growing body of clinical and preclinical evidence has discovered the pivotal role of oxidative stress in their pathogenesis [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%